Patient‐Derived Prostate Cancer Explants: A Clinically Relevant Model to Assess siRNA‐Based Nanomedicines. Issue 6 (4th December 2020) - Tieu, Terence; Irani, Swati; Bremert, Kayla L.; Ryan, Natalie K.; Wojnilowicz, Marcin; Helm, Madison; Thissen, Helmut; Voelcker, Nicolas H.; Butler, Lisa M.; Cifuentes‐Rius, Anna
Abstract: Over the last thirty years, research in nanomedicine has widely been focused on applications in cancer therapeutics. However, despite the plethora of reported nanoscale drug delivery systems that can successfully eradicate solid tumor xenografts in vivo, many of these formulations have not yet achieved clinical translation. This issue particularly pertains to the delivery of small interfering RNA (siRNA), a highly attractive tool for selective gene targeting. One of the likely reasons behind the lack of translation is that current in vivo models fail to recapitulate critical elements of clinical solid tumors that may influence drug response, such as cellular heterogeneity in the tumor microenvironment. This study incorporates a more clinically relevant model for assessing siRNA delivery systems; ex vivo culture of prostate cancer harvested from patients who have undergone radical prostatectomy, denoted patient‐derived explants (PDE). The model retains native human tissue architecture, microenvironment, and cell signaling pathways. Porous silicon nanoparticles (pSiNPs) behavior in this model is investigated and compared with commonly used 3D cancer cell spheroids for their efficacy in the delivery of siRNA directed against the androgen receptor (AR), a key driver of prostate cancer. Abstract : Patient‐derived explants offer a more representative model of solid tumors for the analysis of novel nanoparticle formulations. This platform underlines the importance of understanding how nanoparticles interact with tissue relevant to humans—a key objective in the development of more clinically efficacious nanomedicines.